To solve the formula C = u - k/n for u, we will isolate the variable u on one side of the equation.
C = u - k/n
First, let's get rid of the fraction by multiplying both sides of the equation by n:
n * C = n * (u - k/n)
nC = u * n - k
Next, let's isolate u by adding k to both sides of the equation:
nC + k = u * n
Finally, divide both sides of the equation by n:
(nC + k)/n = u
Therefore, the formula for u in terms of C, k, and n is:
u = (nC + k)/n
Solve the formula for the indicated variable. C = u - k/ n for u
1 answer